(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The aim of the current research is to determine the level of psychosocial adjustment among middle school students (seventh grade), in schools in the Qudsaya suburb area of ​​the Damascus Countryside Education Directorate, and to determine the degree of presence of behavioral problems (school bullying, and classroom disturbance), and then to identify the correlation between the level of Psychosocial adjustment and its relationship to the emergence of behavioral problems. Statistical treatments were used commensurate with the research formula (T-test, arithmetic mean, standard deviation, relative weight), the reliability of the questionnaire using the Cronbach’s alpha equation, and it was applied to students from the seventh grade in middle schools in the Qudsaya suburb area of ​​the Damascus Rural Education Directorate, numbering (10) Schools, as for the categorical variables on which the research was based (gender variable), in addition to measuring the degree of presence of psychosocial adjustment, and the degree of presence of behavioral problems (school bullying, and classroom disturbance). As for the results reached by the study according to the variables that were proposed, they were as follows: There is a statistically significant relationship between psychosocial adjustment and both school bullying and classroom bullying. That is, the higher the level of psychosocial adjustment, the lower the index of behavioral problems (school bullying, classroom bullying) among the student. In the middle school stage, in addition to the absence of a statistically significant difference between the average scores of the answers of the research sample’s seventh-grade students in the Damascus countryside governorate on the social adjustment axis, while a significant and fundamental difference was found between males and females on the psychological adjustment axis, and this difference came in favor of females.